2021
DOI: 10.2147/dddt.s333372
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TRIM8 Protects HK-2 Cells Against Hypoxia/Reoxygenation-Induced Injury by Inhibiting Oxidative Stress-Mediated Apoptosis and Pyroptosis via PI3K/Akt Signal Pathway

Abstract: Background Acute kidney injury (AKI) emerges as an acute and critical disease. Tripartite motif 8 (TRIM8), one number of the TRIM protein family, is proved to participate in ischemia/reperfusion (I/R) injury. However, whether TRIM8 is involved in renal I/R injury and the associated mechanisms are currently unclear. Purpose This study aimed to investigate the precise role of TRIM8 and relevant mechanisms in renal I/R injury. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…In our investigation, the obvious participation of pyroptosis in renal I/R injury was verified by increased expressions of mentioned markers including caspase-1, ASC, NLRP3, GSDMD-N, caspase-11, caspase-4, and IL-1 β in animal and cell models. These findings were in agreement with our published articles [ 25 , 29 ]. Moreover, we innovatively revealed that inhibition of ER stress in renal I/R injury not only considerably relieved renal tissue damage but also successfully mitigated the outbreak of pyroptosis, as evidenced by distinguished alleviation of pyroptosis-related markers mentioned above in the 4-PBA+I/R (or H/R) group compared with the I/R (or H/R) group.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our investigation, the obvious participation of pyroptosis in renal I/R injury was verified by increased expressions of mentioned markers including caspase-1, ASC, NLRP3, GSDMD-N, caspase-11, caspase-4, and IL-1 β in animal and cell models. These findings were in agreement with our published articles [ 25 , 29 ]. Moreover, we innovatively revealed that inhibition of ER stress in renal I/R injury not only considerably relieved renal tissue damage but also successfully mitigated the outbreak of pyroptosis, as evidenced by distinguished alleviation of pyroptosis-related markers mentioned above in the 4-PBA+I/R (or H/R) group compared with the I/R (or H/R) group.…”
Section: Discussionsupporting
confidence: 94%
“…Meanwhile, HK-2 cells in the control group of cellular models were cultured in the normal environment using complete medium with 10% FBS at all times. The 12 h of hypoxia and 4 h of reoxygenation were chosen because our previous studies showed that both apoptosis and pyroptosis were relatively pronounced in such a model [ 25 , 29 ]. Different concentrations of NRG or 4-PBA (5 mM, dilution in DMSO) were added to the medium 24 h before model construction [ 30 ], and then, they were incubated with or without brusatol (400 nM), 2 h before hypoxia [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The KEGG enrichment analysis (Figure D) proved that those 40 intersected genes were primarily enriched in pathways in cancer, MAPK, PI3K-Akt, human cytomegalovirus infection, chemical carcinogenesis-receptor activation pathways, etc. However, the PI3K-Akt pathway activation was testified to protect against the renal I/R injury and to promote the occurrence of renal fibrosis. , Interestingly, the MAPK signaling pathway played a consistent role in the progression of renal I/R and UUO injuries, despite significant differences in the mechanisms of the occurrence and development of acute and chronic kidney diseases. Inhibiting the phosphorylation of MAPK (p38, ERK, and JNK) obviously alleviated kidney damage induced by AKI or renal fibrosis through restraining inflammation and apoptosis. , Furthermore, the PPI network of 40 enriched common targets was analyzed via GENEMANIA (Figure E).…”
Section: Resultsmentioning
confidence: 99%
“…Destructive or persistent pathological circumstances stimulated the unrestrained formation of ROS, leading to harmful disturbance on antioxidative defense and distinguished repression of antioxidant enzymes (SOD, CAT, etc. ). , Excessive and permanent OS inevitably triggered renal cell death by intensifying endoplasmic reticulum stress, pyroptosis, and apoptosis as testified by our published studies. ,,, However, the regulatory mechanisms of oxidative stress in AKI or CKD are not absolutely identical despite the crucial participation of OS. , In recent years, relevant studies frequently demonstrated that suppressing OS would be capable of ameliorating renal fibrosis or AKI to a large extent. Therefore, identifying and targeting the common pathways or molecules seem to be promising and necessary for treating kidney diseases. , Hopefully, some of the antioxidants and anti-inflammation regents have already been tested in clinical trials in patients with relevant kidney diseases and have exhibited encouraging end results. For example, Pablo E Pergola and his colleagues discovered that the oral administration of bardoxolone methyl, one modulator of antioxidant and anti-inflammation, upgraded the estimated glomerular filtration rate in patients along with type 2 diabetes and CKD at 24 weeks .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation